INTERNATIONAL EXPERIENCE AND ISSUES OF IMPROVING NATIONAL LEGISLATION ON COUNTERING EXTREMISM - Sarpekov Рамазан Кумарбекович; Turetskiy Николай Николаевич (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The article examines the legislation of foreign countries – China, Moldova, Belarus, dedicated to countering extremism, as well as the provisions of the Model Law «On Countering Extremism» adopted at the thirty-second plenary session of the Interparliamentary Assembly of the CIS member States; the concepts of «extremism» and «terrorism» in national legislation are analyzed. The authors note that the definition of the concept of «extremism» in the current Law of the Republic of Kazakhstan «On Countering Extremism» has a number of disadvantages that contribute to the confusion of the concepts of «extremism» and «terrorism». This, in turn, generates a number of conflicts in the Criminal Code of the Republic of Kazakhstan: some crimes can be attributed to both extremism and terrorism. And ultimately, this can lead to a distortion of statistics on these crimes. Based on the results of the comparative analysis, it is proposed to introduce a number of novelties into the national legislation on countering extremism, including a new article regulating prosecutor’s supervision as the highest supervision in the field of countering extremism. The authors assign an important place in countering extremism to its prevention. Special attention should be paid to preventive measures among schoolchildren and young people as the most vulnerable and psychologically immature part of the population. In particular, a tangible effect is expected from the introduction of the relevant subject into both the school curriculum and the university education system. In general, among the measures to counter extremism, the authors highlight the improvement of legislation; public involvement in countering extremism; initiatives aimed at promoting intercultural dialogue, increasing media literacy and strengthening interpersonal ties.